Relationship between big five personality profile and quality of life in patients with knee osteoarthritis patients after total knee replacement: a cross-sectional study - Dokman, Gilang Perkasa; Karimah, Azimatul; Edward, Mouli; Atika, Atika (Jurnal Ners, 2026)
Introduction: Knee osteoarthritis (KOA) is a leading cause of disability worldwide; however, the role of personality traits in shaping quality of life (QoL) after total knee replacement (TKR) remains poorly understood, particularly in non-Western populations. This study investigated the relationship between Big Five personality profiles and QoL in patients with KOA who underwent TKR. Methods: This cross-sectional observational study was conducted in 2019–2020 and involved 91 patients who underwent TKR between January 2015 and December 2017. Personality was assessed using the Big Five Inventory-44 (BFI-44), while quality of life was measured using the WHOQOL-BREF. Data were analyzed using Spearman's correlation and Mann–Whitney tests. Results: Most participants were women (74.7%) and aged 63–66 years (69.3%). The predominant personality profile featured low openness (80.2%), high conscientiousness (92.3%), high extraversion (89.0%), high agreeableness (83.5%), and low neuroticism (85.7%). Social relationships scored highest (65.56±7.228) and physical health lowest (58.77±3.442). No significant correlation was found between any personality domain and QoL measures (all p>0.05). Conclusions: No statistically significant relationship was found between Big Five personality profiles and QoL in patients with post-TKR KOA. The observed personality patterns reflect Asian collectivist cultural norms. Physical recovery demands may overshadow personality influences on QoL in this population. Longitudinal studies with larger, culturally diverse samples are warranted.